Intratympanic Treatment in Menière's Disease, Efficacy of Aminoglycosides Versus Corticosteroids in Comparison Studies: A Systematic Review. Issue 1 (January 2020) - Yaz, Furkan; Ziylan, Fuat; Smeeing, Diederik P. J.; Thomeer, Hans G. X. M.
Abstract : Objective: To compare the functional outcomes and complications of intratympanic gentamicin (ITG) versus intratympanic corticosteroids (ITC) in Menière's disease. Data Sources: An electronic search was conducted in the Cochrane Library, PubMed, and Embase databases on February 3, 2019. Articles written in English, Dutch, German, French, or Turkish language were included. Study Selection: Study inclusion criteria were: 1) patients diagnosed with definite Menière's disease according to the criteria of the American Academy of Otolaryngology-Head and Neck Surgery, 2) treated with ITG or ITC in a comparison study, and 3) reported subjective and objective outcomes concerning Menière's disease. Data Extraction: The quality of eligible studies was assessed according to an adjusted version of the Cochrane Risk of Bias tool. The extracted data were study characteristics (study design, publication year, and number of relevant patients), patient's characteristics (sex and age), disease characteristics (uni or bilateral and duration of Menière's disease), treatment protocol, and different therapeutic outcomes (vertigo, tinnitus, aural fullness, and hearing loss). Data Synthesis: A total of eight articles were included for data extraction and analysis. For subjective outcomes, ITG was slightly favored compared to intratympanic corticosteroids. This was significant only in three studies ( p < 0.05). For objective outcomes and complications, no significant differences were seen. Conclusions: The result of this systematic review shows some benefit of ITG over ITC for subjective outcomes and no difference regarding objective outcomes or complication rate. However, this superiority of ITG is rather weak. Both interventions can be effectively and safely used in controlling Menière's disease in acute situations.